Lens Biometry in Congenital Lens Deformities: A Swept-Source Anterior Segment OCT Analysis - Chen, Ze-xu; Jia, Wan-Nan; Jiang, Yong-Xiang (Frontiers in Medicine, 2021)
Aims: To investigate the lens biometric parameters in congenital lens deformities, using a novel technique of swept-source anterior segment optical coherence tomography (SS-ASOCT). Methods: This prospective study included patients with microspherophakia (MSP), coloboma lentis (CL), and posterior lenticonus (PL). For this cohort, 360-degree high-resolution lens images were obtained using the latest SS-ASOCT (CASIA2, Tomey Corp, Nagoya, Japan). The lens biometric parameters were calculated by the CASIA2 built-in software for anterior lens radius (ALR), posterior lens radius (PLR), anteroposterior distance (APD), anterior chamber depth (ACD), equatorial diameter (Eq Dia), rear projection length (RPL), and maximum diameter of the lesion (MDL). Results: This study included two eyes each with MSP and CL and one eye with PL. The lens of MSP was spherical and posteriorly dislocated, with decreased ALR and PLR, Eq Dia, but increased APD. In patients with CL, the coloboma was isolated, bilateral, inferior, and located toward the maldeveloped ciliary body. High astigmatism was mainly lenticular, and this was calculated by the ALR and PLR. Regarding the site of coloboma, a significant decrease in ALR was observed, while the PLR and APD were not affected. The PL eyes had a cone-shaped protrusion of the posterior lens surface with a subtle cataractous region around the apex. An extremely high posterior surface curvature was observed with a mean PLR of 1.67 mm. The RPL and MDL were about 1.80 and 0.4 mm, respectively, which were homogenous at different sections. Conclusions: The CASIA2 is a valuable option for in vivo crystalline lens measurement for congenital lens deformities, enabling the accurate diagnosis and providing illuminating insights into the pathogenesis of MSP, CL, and PL